(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Earnings on the board have been a gigantic and predictable issue among controllers and experts and have pick up critical consideration in the field of bookkeeping. This study focuses on Earnings Management in India. Subsequently, it tends to be inferred that at the time of the investigation, the Companies in the sample and since they are representative, the companies in India are indeed exhibiting Earnings Management Practices. There is additionally solid proof that various companies from various industry segments were bound to practice Earnings Management. The aftereffects of the study are in line with the findings of Nelson et al. (2002). This study has both academic and industry implications as this is forming base for further research in academics and the Industry practioners can have a fair idea of the Earnings management influencing parameters. The limitations of the study can be how representative the sample is and this is overcome by the fact that the samples were chosen in a random manner. Further studies can be conducted on the other financial parameters influencing Earnings management in the Indian context.